Pattern Recognition of Overhead Forehand and Backhand in Badminton Based on the Sign of Local Euler Angle - Muhammad Ilhamdi Rusydi; Syamsul Huda; Febdian Rusydi; Muhammad Hadi Sucipto; Minoru Sasaki (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Studying the badminton skill based on the arm movement is a challenge since the limitation of the sensor such as camera to record the movement parameter. This study proposed a new method to determine the pattern of arm movement for forehand and backhand strokes in badminton based on the sign of the local Euler angle gradient from four points of right arm segments. Each segment was identified by motion sensor attached to the dorsal surface of the hand (sensor 1), wrist (sensor 2), elbow (sensor 3) and shoulder (sensor 4). Three certified coaches participated in this research to determine the arm movement patterns for forehand and backhand strokes. Skills in forehand and backhand strokes from eight professional players and eight amateur players were observed to determine the pattern. The result showed that the local Euler angle can be used to recognize the arm movement pattern. Based on the observed patterns, the professional players had a higher similarity to the coaches’ patterns than those amateur players to the coaches’.